نظـــام تسوية المنازعات في المنظمة العالمية للتجارة - بيــن التراضي والتقاضي - - العـــابد, تــوفيق (جامعة الوادي University of Eloued, 2017)
تتجلى أهمية نظام تسوية المنازعات في المنظمة العالمية للتجارة في إعتماده على تنويع أساليب تسوية المنازعات بين إجبارية وإختيارية، ورضائية وقضائية، فأسلوب المشاورات كإجراء إجباري يجب المرور عليه قبل أي مرحلة من مراحل تسوية النزاع، بالإضافة للأساليب الدبلوماسية التي ترك فيها نظام التسوية الحرية للأطراف في الأخذ بها، كالمساعي الحميدة، الوساطة والتوفيق، وإعتمد على أسلوب التحكيم السريع أيضا كأسلوب إختياري في فض المنازعات. أما الأساليب القضائية فتكون المرحلة الأولى فيها بتشكيل فرق التسوية التي تتصدى لفض النزاع بطلب من أحد الأطراف ويمكن استئناف قراراتها كمرحلة ثانية أمام جهاز الاستئناف الدائم الذي ينظر في الجوانب القانونية التي استند عليها أعضاء الفريق الخاص، وإذا ما تم إعتماد التقرير يلزم الطرف الخاسر بتنفيذه، فإن رفض الامتثال يلجأ الطرف المتضرر لطلب التعويض وتعليق التنازلات ضده. ولا يخلوا هذا النظام من عيوب، فمن أهم نقائصه عدم وضوحه فيما يخص المعاملة التفضيلية للبلدان النامية في كافة مراحل المنازعات The importance of the dispute settlement system in the World Trade Organization is reflected in its reliance on a variety of dispute settlement methods between compulsory, voluntary, consensual and judicial. The method of consultation is compulsory before any stage of dispute settlement, Such as good offices, mediation and conciliation, and also to rely on rapid arbitration as an optional method of settling disputes. Judicial methods are the first stage in forming settlement teams that deal with the resolution of the dispute at the request of one of the parties. Their decisions can be appealed as a second stage before the permanent appellate body, which considers the legal aspects on which the members of the special panel are based Refusal to comply the injured party seeks compensation and suspends concessions against it. The shortcomings of this system are flawed. One of its main shortcomings has its lack of clarity regarding the preferential treatment of developing countries at all stages of conflict.
قــانون أعمال